Asthma randomized trial of indoor wood smoke (ARTIS): Rationale and Methods - Noonan, Curtis W. (2012)
BACKGROUND: Particulate matter (PM) exposures have been linked with poor respiratory health outcomes, especially among susceptible populations such as asthmatic children. Smoke from biomass combustion for residential home heating is an important source of PM in many rural or peri-urban areas in the United States. AIM: To assess the efficacy of residential interventions that reduce indoor PM exposure from wood stoves and to quantify the corresponding improvements in quality of life and health outcomes for asthmatic children. DESIGN: The Asthma Randomized Trial of Indoor wood Smoke (ARTIS) study is an in-home intervention study of susceptible children exposed to biomass combustion smoke. Children, ages 7 to 17, with persistent asthma and living in homes that heat with wood stoves were recruited for this three arm randomized placebo-controlled trial. Two household-level intervention strategies, wood stove replacement and air filters, were compared to a sham air filter placebo. Improvement in quality of life of asthmatic children was the primary outcomes. Secondary asthma-related health outcomes included peak expiratory flow (PEF) and forced expiratory volume in first second (FEV(1)), biomarkers in exhaled breath condensate, and frequency of asthma symptoms, medication usage, and healthcare utilization. Exposure outcomes included indoor and outdoor PM(2.5) mass, particle counts of several size fractions, and carbon monoxide. DISCUSSION: To our knowledge, this was the first randomized trial in the US to utilize interventions targeting residential wood stoves to assess the impact on indoor PM and health outcomes in a susceptible population. TRIAL REGISTRATION: ClincialTrials.gov NCT00807183.